Analyzing the fractal feature of nickel thin films surfaces modified by low energy nitrogen ion: Determination of micro‐morphologies by atomic force microscopy (AFM) - Ţălu, Ştefan; Yadav, Ram Pratap; Ali, Arman; Alireza Grayeli Korpi; Sobola, Dinara; Ţălu, Mihai; Rezaee, Sahare; Achour, Amine; Jurečka, Stanislav; Mardani, Mohsen (Vakuum in Forschung und Praxis : Zeitschrift für Vakuumtechnologie, Oberflèachen und Dünne Schichten, 2019)
Fractal concepts are used to explore how different energies (10, 20 and 50 keV) and fluence of 5 × 1017 N+ cm−2 affect the morphology of nickel thin film. The nickel thin film with thickness of 100 nm is prepared by electron beam evaporation technique at room temperature on stainless steel (AISI 316) substrates. The nanoscale three‐dimensional (3‐D) surface micro‐morphologies are investigated by atomic force microscopy (AFM). Interface width is used to describe the surface height fluctuations. The autocorrelation function with height‐height correlation function give the quantitative data about the morphology of surface. The value of roughness exponent and fractal dimension is computed by height‐height correlation function. Fractal measure is an important analysis which provides fundamental insights into the texture characteristics and a direct way of testing their functional role.